Application of Red Ginger Decorative Compress to Reduce Joint Pain in Osteoarthritis Patients in the Work Area Perumnas Public Health Center Lubuklinggau - Lukman; Nurna Ningsih; Annisa Syahrani (PT FORMOSA CENDEKIA GLOBAL, 2022)
Osteoarthritis is one of the most common types of arthritis, this condition causes joints to feel sore and stiff. Swelling can also occur in these joints. To determine the application of red ginger boiled compresses to reduce joint pain in Osteoarthritis sufferers in the Work Area of ​​the Public Health Center of Lubuklinggau City in 2021. Case study subjects used in family nursing case studies namely 2 families who experience osteoarthritis with knee pain problems on a scale of 4-5, female, 45-70 years old, have members who are more than 15 years old, can communicate well, do not suffer from complications of other diseases and do not take medication. Before the action is taken. Research results: during the application of red ginger decoction compresses are able to provide a comfortable effect and help in overcoming joint inflammation that occurs. The application of red ginger boiled compresses can reduce joint pain in osteoarthritis sufferers.